Case Report: Post-splenectomy bulky pelvic splenosis in an adolescent with hereditary spherocytosis - Di Majo, Benedetta Elena; Peccatori, Nicolò; Inzoli, Alessandra; Degrate, Luca; Jaconi, Marta; Ratti, Michele; Casiraghi, Alessandra; Ferrari, Giulia Maria; Sala, Debora; Biondi, Andrea; Passoni, Paolo; Corti, Paola (Frontiers in Pediatrics, 2025)
Splenectomy is a well-established therapeutic approach for pediatric hematologic disorders, especially in the case of hereditary spherocytosis (HS). In addition to the commonly acknowledged short- and long-term infectious and thrombotic complications, also splenosis represents a rare but noteworthy complication of splenectomy. Splenosis is characterized by the auto-transplantation and growth of splenic tissue in ectopic locations, following trauma or splenectomy. This condition can mimic malignancies, posing diagnostic challenges. We report the case of a 16-year-old girl with HS who presented with fever, abdominal pain, and a history of laparoscopic splenectomy ten years early. Imaging revealed a vascularized pelvic mass, initially suspected to be malignant. Diagnostic laparoscopy and histopathological analysis confirmed the mass as pelvic splenosis. The patient was asymptomatic, prompting a conservative management approach with regular follow-up. This case highlights the importance of considering splenosis in differential diagnoses for pelvic masses in patients with prior splenectomy, to ensure appropriate management and avoid unnecessary interventions.